Coxiella Burnetii Acute Cerebellitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A 9-year-old boy presenting with headache and fever, followed after 10 days by drowsiness, conjugate ocular deviation, and subsequently, cerebellar ataxia, is reported from Akita University, Japan.